Challenging Security Issues Using BIG Data on Mobile Application Development - Guptha1K Gurnadha; V Vuna, Vidya Sagar; GOPAIAH, J.; Goud, K Ram Mohan; Anuradha, K (IJRDO -Journal of Computer Science Engineering, 2015)
The present paper highlights big data-specific security, privacy challenges, high volume inter-cloud computing, Big data, Hadoop Environment to the various rules determined by the actions taken by various organizations and companies benefit large scale and small scale industries. They promise new frontiers in science. Some companies are able to use big data for high efficiency. Security and privacy are focus by velocity, volume, and variety of big data, Cloud infrastructures, and distinct sources of data and stream of nature of acquisition. Mobile devices have virtually become many people’s fifth appendage. The result is a huge flow of data from Smart-phones and tablets to organizations, which are struggling to manage and utilize that information. The traditional security mechanism are tailored to secure small-scale static opposes and stream data inadequacy. Expectations highlight challenges and bring renewed focus fortifying big data infrastructures. Cloud computing security includes rapid pace to computer security, network security, information security and data privacy. Data is protected in large and related infrastructure with policies, technologies, controls and big data tools. Mobile today can build applications which understand the users to work with the information and help in providing advice and recommendations.